Analysis of Stability and Differential Settlement of Existing Embedded Construction in Stages (Case Study: Sidoarjo Muddle Embedded (LuSi) - Parwita*, Dewa Ngakan Putu Ananda; Soemitro, Ria Asih Aryani; Satrya, Trihanyndio Rendy (Universitas Syiah Kuala, 2023)
In May 2006, a mud eruption occurred in Sidoarjo, East Java, Indonesia, prompting the construction of embankments to contain the affected area. Due to the continuous eruption of mud, the embankment's storage capacity has reached its limit, and it has been raised continuously in stages. Unfortunately, underlying soft clay remains unreinforced, posing a risk of failure. Previous research results indicate that consolidation is still ongoing, and settlement is predicted to continue for decades. To address these issues, researchers used finite element method analysis, Plaxis 2D, to analyze the effects of embankment construction stages and consolidation processes on embankment stability. Research objectives include settlement, safety factors, and consolidation duration. The analysis results on the model are compared with journal findings (Whittle et al., 2022). Based on the research, it is found that with precisely the same input data, there are differences in safety factor and settlement values, but they exhibit similar behavior. After the validation process, it is obtained that a change from Undrained B drainage type to Undrained A is needed, with different data requirements. Effective cohesion (c') of 17 kPa and effective internal friction angle (') of 14 are used as new input data. The settlement and safety factor behavior based on this input data shows similar values. The largest differential settlement occurs at the middle of the embankment (X = 79 m), and the smallest is downstream (X = 40 m) when the construction reaches the fifth stage. The consolidation duration is 18,590 days with a predicted maximum settlement of 9.096 m